2013
DOI: 10.1007/s11192-013-0952-5
|View full text |Cite
|
Sign up to set email alerts
|

Can a personal website be useful as an information source to assess individual scientists? The case of European highly cited researchers

Abstract: The Web is not only the main scholarly communication tool but also an important source of additional information about the individual researchers, their scientific and academic activities and their formally and informally published results. The aim of this study is to investigate whether successful scientists use their personal websites to disseminate their work and career details and to know which specific contents are provided on those sites, in order to check if they could be used in research evaluation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Today, academic standing may be linked to online standing: a researcher's online presence is an important channel for dissemination of expertise and achievements (Genoni et al, 2005;Mas-Bleda and Aguillo, 2013). Many researchers feel it is important to have a strong online presence in addition to having high quality publications in order to make a scientific impact.…”
mentioning
confidence: 99%
“…Today, academic standing may be linked to online standing: a researcher's online presence is an important channel for dissemination of expertise and achievements (Genoni et al, 2005;Mas-Bleda and Aguillo, 2013). Many researchers feel it is important to have a strong online presence in addition to having high quality publications in order to make a scientific impact.…”
mentioning
confidence: 99%
“…Availability of the articles on author personal website (Antelman, 2004;Más-Bleda & Aguillo, 2013) Deposit the paper in the institutional repository (Tate, 2010;Ngah, 2010;Koulouris et al, 2013) …”
Section: Methodsmentioning
confidence: 99%
“…The World Wide Web has become an outstanding tool for the collection and dissemination of scholarly Information (Más-Bleda & Aguillo, 2013). The majority of freely available articles will be found on author personal website rather than in a repository or in an open-access journal (Antelman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Self-archiving: One of the ways of self-archiving accepted article is through creation of personal websites that makes the article open access, thereby increasing its impact and citations. Personal websites are created by individual researchers where they post information regarding their article along with their personal details, a Curriculum Vitae, list of publications, research interest, experience and expertise, and research projects and conference presentations [10]; thereby, making it a channel that projects their work. It has been found that open access repositories have a lower proportion of citations [11] as compared to personal websites, but the effectiveness of such self-publishing is questionable [12].…”
Section: Blowing Your Own Trumpetmentioning
confidence: 99%